Transjugular Intrahepatic Portosystemic Shunt before Abdominal Surgery in Cirrhotic Patients: A Retrospective, Comparative Study - Evelyne Vinet; Pierre Perreault; Louis Bouchard; Denis Bernard; Ramses Wassef; Carole Richard; Richard Létourneau; Gilles Pomier-Layrargues (Canadian Journal of Gastroenterology)
Surgery in cirrhotic patients is associated with high morbidity and mortality related to portal hypertension and liver insufficiency. Therefore, preoperative portal decompression is a logical approach to facilitate abdominal surgery and hopefully to improve postoperative survival. The present study evaluated the clinical outcomes of 18 patients (mean age 58 years) with cirrhosis (seven alcoholics and 11 nonalcoholics) who underwent transjugular intrahepatic portosystemic shunt (TIPS) placement before antrectomy (n=5), colectomy (n=10), small-bowel resection (n=1), pancreatectomy (n=1) and nephrectomy (n=1). TIPS was performed a mean (± SD) of 72±21 days before surgery and induced a marked mean decrease in portohepatic gradient from 21.4±3.9 mmHg to 8.4±3.4 mmHg. Cirrhotic patients (n=17) who underwent elective abdominal surgery without preoperative TIPS placement were used as the control group. Both groups were matched for age, etiology of cirrhosis, indications for surgery, type of surgery and coagulation parameters. The mean Pugh score was significantly higher in the TIPS group (7.7 versus 6.2). No significant differences were observed for operative blood loss, postoperative complications, duration of hospitalization and one-month (83% versus 88%) or one-year (54% versus 63%) cumulative survival rate. Analysis using the Cox proportional hazards model showed that neither TIPS placement nor preoperative Pugh score were independent predictors for survival. The present study suggests that preoperative TIPS placement does not improve postoperative evolution after abdominal surgery in cirrhotic patients with good or moderately impaired liver function.